Pengaruh Model Pembelajaran Metakognitif Terhadap Kemampuan Pemecahan Masalah Matematis - Muhammad Bayu Al Dhana; Nurullita Astriani (Jurnal THEOREMS (The Original Research of Mathematics), 2023)
Metacognitive learning can help students develop their knowledge so that they can improve cognitive activity, especially in learning mathematics. In learning mathematics the ability to solve mathematical problems is a fundamental and very important problem solving ability. The purpose of this study is to determine the effect of the metacognitive learning model on mathematical problem solving abilities. This research is a quantitative research with a quasi-experimental type. The population in this study were all students of class IX at SMP Negeri 1 Pangkalan Susu. The sample in this study consisted of 2 classes, namely class IX-1 which was used as the experimental class and class IX-2 which was used as the control class. This study involved a type of instrument, namely a test in the form of a description test on congruence and similarity. This shows that there is an influence of the metacognitive learning model on mathematical problem solving abilities.Â